Dare to lead : brave work, tough conversations, whole hearts - Brown, Brené (Random House, 2018)
Leadership is not about titles, status, and wielding power. A leader is anyone who takes responsibility for recognizing the potential in people and ideas, and has the courage to develop that potential. When we dare to lead, we don<U+2019>t pretend to have the right answers; we stay curious and ask the right questions. We don<U+2019>t see power as finite and hoard it; we know that power becomes infinite when we share it with others. We don<U+2019>t avoid difficult conversations and situations; we lean into vulnerability when it<U+2019>s necessary to do good work. But daring leadership in a culture defined by scarcity, fear, and uncertainty requires skill-building around traits that are deeply and uniquely human. The irony is that we<U+2019>re choosing not to invest in developing the hearts and minds of leaders at the exact same time as we<U+2019>re scrambling to figure out what we have to offer that machines and AI can<U+2019>t do better and faster. What can we do better? Empathy, connection, and courage, to start.